Pendidikan Empati: Kontribusi Pandangan Edith Stein bagi Rekonstruksi Mata Pelajaran Pendidikan Agama Katolik di Indonesia - Watratan, Elisabeth; Fatlolon, Costantinus (Media: Jurnal Filsafat dan Teologi, 2025)
Empathy has become an integral component of the contemporary educational curriculum. This study has been formulated as a review of literature employing a critical-exposition methodology to examine Edith Stein's ideas on empathy and education, as well as her impact on Catholic Religious Education (CRE). The primary objective is to elucidate Stein's perspectives on empathy and education with the purpose of enhancing religious educational practices and fostering empathy in both educators and students within Catholic educational institutions. The fundamental inquiry of this research is: "What role does Edith Stein's concepts of empathy and education play in shaping Catholic Religious Education?" The results of this analysis indicate that Stein's beliefs regarding empathy as a deliberate effort to comprehend others' experiences and education as a structured endeavor to humanize students in all facets are particularly significant in reforming CRE within Catholic schools at primary and secondary levels in Indonesia. Key aspects include a comprehensive anthropological outlook, well-defined and sustainable educational objectives, tailored instructional materials reflecting students' interests, abilities, and circumstances, experiential teaching methods, and the essential traits of humility, faithfulness, and adherence to Church teachings in educators.